2005
DOI: 10.3846/16486897.2005.9636857
|View full text |Cite
|
Sign up to set email alerts
|

Investigation and Evaluation of Landfill Leachate Permeability in the Soil

Abstract: Today waste management is one of the most important environmental problems, danger that used landfills and their collected leachate can cause. This paper analyses the filtration coefficient of soils typical of landfill assessment by air conditions and different density of soils. Heavy metal concentrations were determined by using the flame absorption spectrometric method. Besides, the results of modeling heavy metal permeability are presented here. Dependence of heavy metal permeability characteristics on soil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
1
0
2
Order By: Relevance
“…Studies on the effect of leachate from a landfill to the underground water (often used for extraction for potable water; or, discharged to rivers) of the surrounding area demonstrated that underground water quality has been compromised by such leachate (Vasarevičius et al 2005;Hossain et al 2014). This potential public health hazard to potable water resources cannot be ignored.…”
Section: Problems Of Environmental Inventory Of Old Small Landfillsmentioning
confidence: 99%
“…Studies on the effect of leachate from a landfill to the underground water (often used for extraction for potable water; or, discharged to rivers) of the surrounding area demonstrated that underground water quality has been compromised by such leachate (Vasarevičius et al 2005;Hossain et al 2014). This potential public health hazard to potable water resources cannot be ignored.…”
Section: Problems Of Environmental Inventory Of Old Small Landfillsmentioning
confidence: 99%
“…Kairių sąvartyno filtrate nustatyti sunkieji metalai: Cu, Zn, Ni, Cr, Pb, Hg, Cd, Mn, Co (Montvydienė et al 2014;Vasarevičius et al 2005).…”
Section: įVadasunclassified
“…Esant didesnei srovei kolmatacijos procesai ir turėtų sulėtėti, tačiau susidarantis didesnis filtrato kiekis taip pat nėra teigiamas reiškinys. Nors daugelyje sąvartynų diegiamos filtrato recirkuliacinės sistemos, tačiau, koks jų poveikis kolmatacijai, sąvartyno dugno apsauginiams sluoksniams, nėra ištirta (Celiad et al 2000;Ettler 2008;Petraitis 2009;Sinan et al 2006;Vasarevičius et al 2005).…”
Section: Filtrato Sudėties Kaitos Tyrimai Ir Jų Analizėunclassified